Kevlar®, Nomex®, and VAR Modification by Small Organic Molecules Anchoring: Transfusing Antibacterial Properties and Improving Water Repellency - Efrosyni Frousiou; Efstathios Tonis; Georgios Rotas; Anna Pantelia; Savvas G. Chalkidis; Nikolaos S. Heliopoulos; Antonia Kagkoura; Dionysios Siamidis; Angeliki Galeou; Anastasia Prombona; Kostas Stamatakis; Nikos Boukos; et al. (Molecules, 2023)
The surface modification of fabrics composed of Kevlar®, Nomex®, or VAR was extensively investigated. Kevlar® and Nomex® are widely-utilized aramid materials, whereas VAR is a technical fabric comprising 64% viscose, 24% para-aramid (Kevlar®), 10% polyamide, and 2% antistatic fibers. Both aramid materials and cellulose/viscose exhibit exceptional mechanical properties that render them valuable in a wide range of applications. For the herein studied modification of Kevlar®, Nomex®, and VAR, we used small organic molecules 3-allyl-5,5-dimethylhydantoin (ADMH) and 3-(acrylamidopropyl)trimethylammonium chloride (APTAC), which were anchored onto the materials under study via graft polymerization. By doing so, excellent antibacterial properties were induced in the three studied fabrics. Their water repellency was improved in most cases as well. Extensive characterization studies were conducted to probe the properties of the modified materials, employing Raman and FTIR spectroscopies, Scanning Electron Microscopy (SEM), and thermogravimetric analysis (TGA).